Differences in cricket fast bowling kinematics between grass and artificial surface pitches - Alway, P.; Felton, P.; James, I.; King, M.; McErlain-Naylor, K. (Sports Biomechanics, 2025)
Cricket fast bowling training and research are often conducted on artificial turf, while matches are played on natural grass. It is unknown if technique differs between the different surfaces; therefore, the aim of this study was to explore if fast bowling technique differed between surfaces. Shoe slip distance and kinematic and temporal parameters previously associated with ball release velocity and lumbar bone stress injury were determined for eight male sub-elite fast bowlers using three-dimensional motion analysis on grass and artificial surfaces. Paired t-test and statistical parametric mapping were used to identify differences in technique between surfaces. Significantly greater slip distance was observed during back and front foot contact on the artificial surface compared to bowling on the grass surface. No kinematic or temporal parameter significantly differed between surfaces, therefore fast bowling technique is likely similar between grass and artificial surfaces, and previous research utilising artificial surfaces in fast bowling research is likely to be valid.